Lipoprotein Subfraction Profile and HDL‐Associated Enzymes in Sickle Cell Disease Patients. Issue 12 (11th October 2013) - Ozturk, Oktay H.; Can, Yesim; Yonden, Zafer; Motor, Sedat; Oktay, Gonul; Kaya, Hasan; Aslan, Mutay
Abstract: Although hypocholesterolemia is a reported finding in sickle cell disease (SCD), low‐density lipoprotein (LDL)/high‐density lipoprotein (HDL) subfractions and HDL‐associated enzymes have not been determined in SCD patients. Blood was collected from 38 hemoglobin (Hb)A volunteers and 45 homozygous HbSS patients who had not received blood transfusions in the last 3 months. Serum lipids were measured by automated analyzer while LDL and HDL subfraction analysis was done by continuous disc polyacrylamide gel electrophoresis. Serum levels of cholesteryl ester transfer protein (CETP), lecithin‐cholesterol acyltransferase (LCAT), apolipoprotein B (apoB) and apolipoprotein A‐1 (apoA‐I) were determined by enzyme‐linked immunosorbent assay (ELISA). Total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐C) and high‐density lipoprotein cholesterol (HDL‐C) levels were significantly decreased, while TG levels were significantly increased in SCD patients compared to controls. A significant decrease in intermediate‐density lipoprotein (IDL)‐C, IDL‐B, IDL‐A and LDL‐1 fractions were seen in SCD patients, while no significant difference was observed in small dense LDL particles. A significant decrease was seen in HDL‐large, HDL‐intermediate and HDL‐small fractions in SCD patients versus controls. Levels of LCAT and ApoA‐1 protein measured in SCD patients were significantly lower while no significant difference was observed in CETP and ApoB protein levels compared to controls. The reduction observed in LDL‐ and HDL‐C in SCD patients was reflected as significantly decreased IDL, LDL‐1 and HDL‐subfractions. Decreased HDL subfractions may possibly lead to the reduced ApoA‐1 and LCAT protein levels observed in SCD patients.